KETERKAITAN ANTARA DIMENSI PERKEMBANGAN KARIR, KOMITMEN AFEKTIF, DAN TURNOVER INTENTION - Syahrial, Yoppi; Putra, Ardian Prima; Wijayanti, Ariyani Wahyu (STIE Atma Bhakti, 2019)
This study examines the relationship of four dimensions in career development those are increased career goals, professional ability, promotion speed and increased remuneration, toward an affective commitment, and a turnover intention. The sample is employees of PT. Aksara Solopos in the amount of 100 respondents. A survey method was used in this study to be data collection method and it was done by distributing questionnaires directly to respondents. Structural Equation Modeling (SEM) was used for data analysis and the results show that the dimensions of career development.The method of data collection in this study used a survey method by distributing questionnaires directly to respondents. Data analysis using Structural Equation Modeling (SEM). The test results show that the dimensions of career development (increased career goals, professional ability, promotion speed and increased remuneration) influence increased career goals, professional ability, promotion speed and increased remuneration, furthermore that affective commitment negatively influence turnover intention.